Preparation and application of gamma-ray radiation resistant miscellaneous element modified polyimide resin coating

By introducing fluorine or boron element monomers into the polyimide material, a heterogeneous modified polyimide resin is formed and combined with lubricating functional fillers, the aging and mechanics of the polyimide material under nuclear radiation environment is solved. The problem of performance decay has achieved improved radiation resistance and lubrication performance of the material.

CN119177083AActive Publication Date: 2024-12-24LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411496618.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-24
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

Polyimide materials will undergo radiation degradation in long-term and large-dose nuclear radiation environments, resulting in the material aging, hardening, brittleness, and deterioration of mechanical properties. The existing technology has failed to essentially introduce functional fillers through multi-layer structure design and introduction of functional fillers. Improve its nuclear radiation resistance.

Method used

Through the host-guest polycondensation reaction strategy, elemental monomers such as fluorine or boron containing neutron absorption are introduced into the polyimide prepolymer in situ to form heterogeneous elements modified polyimide resin, combined with lubricating functional fillers. Radiation-resistant lubricating materials with excellent mechanical properties and lubricating protection properties were prepared.

Benefits of technology

It significantly improves the nuclear radiation resistance and tribological properties of polyimide materials, extends the service life, and maintains good comprehensive mechanical properties and lubricating properties in high radiation environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177083A_ABST
    Figure CN119177083A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of a gamma-ray radiation resistant miscellaneous element modified polyimide resin coating, and belongs to surface protection in a nuclear radiation environment. The hetero-element modified polyimide resin coating is a bonding solid protective coating material with excellent nuclear irradiation resistance, which is obtained by introducing a fluorine-containing or boron-containing monomer with a neutron absorption effect into a polyimide precursor in situ to form hetero-element modified polyimide resin and then compounding a filler with a lubricating function. The miscellaneous element modified polyimide coating not only has good comprehensive mechanical properties and lubrication protection performance, but also still shows excellent comprehensive mechanical properties and lubrication protection performance after being irradiated by a large dose of gamma rays (the accumulated irradiation dose is 1000kGy); the modified polyimide material can be used for surface protection of related moving parts in a long-term nuclear radiation environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of radiation protection, and in particular relates to the preparation and application of a heteroelement-modified polyimide resin resistant to gamma-ray radiation. Background Art

[0002] Polyimide materials themselves have good thermal stability, mechanical properties, light weight and flexibility, easy molding and processing, and radiation resistance. They are widely used in extreme working conditions such as aerospace and nuclear energy. However, in a long-term, high-dose nuclear radiation environment, polyimide materials will still undergo radiation degradation, causing the material to age and become hard and brittle, with severe decline in mechanical properties, reduced service life, and failure in a short period of time (J. Nucl. Mater., 1987, 148, 53-60; J. Phys.: Conf. Ser., 2020, 1622, 012026; New ChemMater, 2023, 51(10):156-160). Therefore, further improving the mechanical properties and radiation resistance of polyimide through molecular structure design and modification has important scientific significance and engineering value for its practical application. Chinese patent (CN202111067932.4) discloses a radiation-resistant polyimide with a sandwich structure and its preparation method and application, which achieves the purpose of improving radiation resistance through a multilayer structure design idea. Chinese patent (CN201910744025.5) discloses a method for improving the radiation resistance of polyimide composite film by using modified boron nitride; similarly, Chinese patent (CN201910489096.5) discloses a neutron radiation-proof polyimide coating and its preparation method and application, which mainly reacts cyanoborane triamine with anhydride-terminated polyimide oligomer to obtain hyperbranched polyimide, and then obtains it by adding functional slow neutron adsorption compounds and silane coupling agents for ball milling and blending. It can be seen that the prior art improves the radiation resistance of composite materials by means of multilayer structure design and the introduction of functional fillers, and does not essentially improve the nuclear radiation resistance of polyimide base resin. Summary of the invention

[0003] The present invention aims to provide a method for preparing a gamma-ray radiation-resistant modified polyimide resin containing impurity elements, which mainly utilizes a host-guest condensation reaction strategy to in-situ introduce neutron-absorbing monomers containing fluorine or boron or other elements into a polyimide prepolymer at a molecular level, thereby substantially improving the nuclear radiation resistance stability of the polyimide base resin and obtaining a modified polyimide prepolymer having both excellent mechanical properties and good radiation resistance; and using the modified polyimide prepolymer as a base resin binder and compounding different lubricating functional fillers, a radiation-resistant lubricating material having excellent mechanical properties and lubricating protective properties is obtained.

[0004] The preparation method of the gamma-ray radiation-resistant impurity-containing modified polyimide resin coating of the present invention is based on a host-guest condensation reaction strategy, wherein impurity-containing monomers are in situ introduced into a polyimide precursor to obtain an impurity-containing modified polyimide resin with good radiation resistance; and the impurity-containing modified polyimide resin is used as a base resin binder, and a radiation-resistant lubricating coating with excellent comprehensive mechanical properties and lubrication protection properties is obtained by compounding functional fillers.

[0005] The heteroelement-containing monomer is one or two of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 4-aminoformylphenylboronic acid, and 4-aminophenylboronic acid pinacol ester.

[0006] The polyimide precursor is a mixture of a diamine monomer 4,4-diaminodiphenyl ether and a dianhydride monomer 3,3'4,4'-diphenyl ether tetracarboxylic dianhydride.

[0007] The in-situ introduction process is as follows: dissolving the diamine monomer 4,4-diaminodiphenyl ether and the monomer containing heteroelement in an organic solvent and stirring and mixing them evenly, then adding the dianhydride monomer 3,3'4,4'-diphenyl ether tetracarboxylic dianhydride in batches under nitrogen protection, and stirring and reacting for 20 to 30 hours at -20 to 15°C. The molar ratio of the diamine monomer to the monomer containing heteroelement is 2:1 to 18:1, the molar ratio of the dianhydride monomer to the diamine monomer is 1:1 to 1.5:1, and the organic solvent is N,N-dimethylformamide or N,N-dimethylacetamide that has been dehydrated.

[0008] The specific preparation process of the radiation-resistant lubricating coating is as follows: using heteroelement-modified polyimide resin as a basic resin binder, a mixture of molybdenum disulfide and lanthanum trifluoride ground 2 to 3 times on a conical mill as a functional filler, and a mixed solvent of N,N-dimethylformamide and N-methylpyrrolidone as a diluent, and obtaining a radiation-resistant lubricating coating with a solid content of 30% to 40% after high-speed shearing. The molar ratio of molybdenum disulfide to lanthanum trifluoride is 3:1 to 5:1, and the volume ratio of N,N-dimethylformamide to N-methylpyrrolidone is 1:2 to 2:1.

[0009] Another object of the present invention is to disclose the application of the gamma-ray radiation-resistant impurity-element-modified polyimide resin coating in radiation-resistant coating.

[0010] The specific preparation process of the radiation-resistant coating is as follows: the coating is sprayed on the metal substrate by a spray gun, and then kept at 130-150° C. for 1-2 hours, and heated and cured at 270-290° C. for 1-2 hours to obtain the coating.

[0011] The radiation-resistant coating obtained by the present invention was subjected to a gamma-ray irradiation test, with total irradiation doses of 300 kGy and 1000 kGy, respectively. The mechanical properties and tribological properties before and after irradiation were tested, and the surface micromorphology changes of the coating before and after irradiation were observed using a scanning electron microscope.

[0012] The specific test method is as follows: Mechanical properties test: Tested in accordance with ISO 527:2019; Tribological properties: The atmospheric friction and wear properties of the coatings before and after irradiation were tested using a CSM friction tester. The test conditions were a rotation mode with a rotation radius of 0.5 cm, a linear speed of 5 cm / s, a load of 5 N, and a Φ6 mm GCr15 steel ball as the dual ball.

[0013] The test results show that the heteroelement-modified polyimide film prepared by the present invention has good γ-ray radiation resistance ( Figure 1-2 ), after the unmodified polyimide film was irradiated with a dose of 1000kGy, the surface color became darker and the aging phenomenon was serious, while the color of the modified film remained unchanged after irradiation. At the same time, the tensile test showed that the tensile strength and elongation at break of the modified film did not change significantly after γ-ray irradiation; the comparison of the tribological properties under different radiation doses showed that the modified polyimide composite coating not only had a lower friction coefficient and wear rate ( Figure 3-5 ), and γ-ray irradiation has no obvious effect on its tribological properties.

[0014] In summary, the present invention has the following beneficial effects: The modified polyimide lubricating composite coating of the present invention forms a highly cross-linked macromolecular network structure by introducing fluorine or boron element polymer monomers in a chemical polycondensation manner, which improves the tensile strength and elongation at break of the polyimide material itself and reduces the friction coefficient and wear rate; at the same time, the fluorine, boron and phenolic hydroxyl groups in the molecular structure have good radiation inhibition effects, can effectively block external radiation, and improve the nuclear radiation resistance of polyimide, so that the modified polyimide composite coating still has good comprehensive mechanical properties and tribological properties under long-term nuclear radiation. In addition, the modified polyimide lubricating composite coating material of the present invention is simple to obtain, simple to make, and has a short production cycle, and is suitable for industrial production and large-scale engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The macroscopic surface morphologies of the modified polyimide (BPI15) and pure polyimide film (PI) prepared in Example 1 and Comparative Example 1 before and after irradiation.

[0016] Figure 2The microstructure morphology of the modified polyimide (BPI15) and pure polyimide film (PI) prepared in Example 1 and Comparative Example 1 before and after radiation.

[0017] Figure 3 This is the friction coefficient change curve of the coating material prepared in Example 1 before and after irradiation.

[0018] Figure 4 The friction coefficient change curve of the coating material prepared in Comparative Example 1 before and after irradiation.

[0019] Figure 5 The wear rate changes of the coating materials prepared in Example 1 and Comparative Example 1 under different radiation doses. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is further described in detail below in conjunction with several embodiments and drawings, but is not limited to the following embodiments.

[0021] Example 1 The diamine monomer 4,4-diaminodiphenyl ether (5.41 g, 0.027 mol) and 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (1.10 g, 0.003 mol) were added to the dehydrated N,N-dimethylformamide solvent, transferred to a three-necked flask and nitrogen was introduced for protection. After mechanical stirring, the dianhydride monomer 3,3'4,4'-diphenyl ether tetracarboxylic dianhydride (9.31 g, 0.03 mol) was slowly added in batches to control the total molar amount of dianhydride to diamine monomer to be 1.01:1. Before the anhydride monomer is added, ensure that the solution is in an ice-water bath environment. After the anhydride monomer is completely added to the solution, remove the ice-water bath, and react under mechanical stirring at room temperature for 24 hours to obtain a light yellow viscous solution. According to the requirements for test piece size in the ISO 527:2019 test standard, the modified polyimide film after curing at 140°C for 1 hour and 280°C for 1 hour is cut into standard tensile test pieces for subsequent tensile tests.

[0022] At the same time, the obtained light yellow viscous liquid is used as the base resin binder, and a mixture of molybdenum disulfide and lanthanum trifluoride (the molar ratio of molybdenum disulfide to lanthanum trifluoride is 4:1) that has been ground and dispersed in advance is compounded as a functional filler, and the total mass ratio of the modified resin binder to the functional filler is controlled to be approximately 3:8. Then, a mixed solvent of N,N-dimethylformamide and N-methylpyrrolidone with a volume ratio of 1:1 is used to adjust the total solid content of the coating to 35%, and a liquid lubricating composite coating is obtained. After the coating is sprayed on a metal substrate with a spray gun, it is heated and cured at 140°C for 1 hour and at 280°C for 1 hour to obtain a coating material.

[0023] Example 2 The diamine monomer 4,4-diaminodiphenyl ether (5.41 g, 0.027 mol) and 4-carbamoylphenylboronic acid (0.49 g, 0.003 mol) were added to the dehydrated N,N-dimethylformamide solvent, transferred to a three-necked flask and nitrogen was introduced for protection. After mechanical stirring, the dianhydride monomer 3,3'4,4'-diphenyl ether tetracarboxylic dianhydride (9.31 g, 0.03 mol) was slowly added in batches to control the total molar amount of dianhydride to diamine monomer to be 1.01:1. Before the anhydride monomer is added, ensure that the solution is in an ice-water bath environment. After the anhydride monomer is completely added to the solution, remove the ice-water bath. After mechanical stirring at room temperature for 24 hours, a light yellow viscous solution is obtained. According to the requirements for test piece size in the ISO 527:2019 test standard, the modified polyimide film that has been cured by keeping it at 140°C for 1 hour and at 280°C for 1 hour is cut into standard tensile test pieces for subsequent tensile tests.

[0024] At the same time, the obtained light yellow viscous liquid is used as the base resin binder, and a mixture of molybdenum disulfide and lanthanum trifluoride (the molar ratio of molybdenum disulfide to lanthanum trifluoride is 4:1) that has been ground and dispersed in advance is compounded as a functional filler, and the total mass ratio of the modified resin binder to the functional filler is controlled to be approximately 3:8. Then, a mixed solvent of N,N-dimethylformamide and N-methylpyrrolidone with a volume ratio of 1:1 is used to adjust the total solid content of the coating to 35%, and a liquid lubricating composite coating is obtained. After the coating is sprayed on a metal substrate with a spray gun, it is heated and cured at 140°C for 1 hour and at 280°C for 1 hour to obtain a coating material.

[0025] Example 3 The diamine monomer 4,4-diaminodiphenyl ether (5.41 g, 0.027 mol) and 4-aminophenylboronic acid pinacol ester (0.66 g, 0.003 mol) were added to the dehydrated N,N-dimethylformamide solvent, transferred to a three-necked flask and nitrogen was introduced for protection. After mechanical stirring, the dianhydride monomer 3,3'4,4'-diphenyl ether tetracarboxylic dianhydride (9.31 g, 0.03 mol) was slowly added in batches to control the total molar amount of dianhydride and diamine monomer to be 1.01:1. Before the anhydride monomer is added, ensure that the solution is in an ice-water bath environment. After the anhydride monomer is completely added to the solution, remove the ice-water bath. After mechanical stirring at room temperature for 24 hours, a light yellow viscous solution is obtained. According to the requirements for test piece size in the ISO 527:2019 test standard, the modified polyimide film that has been cured by keeping it at 140°C for 1 hour and at 280°C for 1 hour is cut into standard tensile test pieces for subsequent tensile tests.

[0026] At the same time, the obtained light yellow viscous liquid is used as the base resin binder, and a mixture of molybdenum disulfide and lanthanum trifluoride (the molar ratio of molybdenum disulfide to lanthanum trifluoride is 4:1) that has been ground and dispersed in advance is compounded as a functional filler, and the total mass ratio of the modified resin binder to the functional filler is controlled to be approximately 3:8. Then, a mixed solvent of N,N-dimethylformamide and N-methylpyrrolidone with a volume ratio of 1:1 is used to adjust the total solid content of the coating to 35%, and a liquid lubricating composite coating is obtained. After the coating is sprayed on a metal substrate with a spray gun, it is heated and cured at 140°C for 1 hour and at 280°C for 1 hour to obtain a coating material.

[0027] Example 4 The diamine monomer 4,4-diaminodiphenyl ether (9.42 g, 0.047 mol) and 4-aminophenylboronic acid pinacol ester (0.66 g, 0.003 mol) were added to the dehydrated N,N-dimethylformamide solvent, transferred to a three-necked flask and nitrogen was introduced for protection. After mechanical stirring, the dianhydride monomer 3,3'4,4'-diphenyl ether tetracarboxylic dianhydride (15.52 g, 0.05 mol) was slowly added in batches to control the total molar amount of dianhydride and diamine monomer to be 1.01:1. Before the anhydride monomer is added, ensure that the solution is in an ice-water bath environment. After the anhydride monomer is completely added to the solution, remove the ice-water bath. After mechanical stirring at room temperature for 24 hours, a light yellow viscous solution is obtained. According to the requirements for test piece size in the ISO 527:2019 test standard, the modified polyimide film that has been cured by keeping it at 140°C for 1 hour and at 280°C for 1 hour is cut into standard tensile test pieces for subsequent tensile tests.

[0028] At the same time, the obtained light yellow viscous liquid is used as the base resin binder, and a mixture of molybdenum disulfide and lanthanum trifluoride (the molar ratio of molybdenum disulfide to lanthanum trifluoride is 4:1) that has been ground and dispersed in advance is compounded as a functional filler, and the total mass ratio of the modified resin binder to the functional filler is controlled to be approximately 3:8. Then, a mixed solvent of N,N-dimethylformamide and N-methylpyrrolidone with a volume ratio of 1:1 is used to adjust the total solid content of the coating to 35%, and a liquid lubricating composite coating is obtained. After the coating is sprayed on a metal substrate with a spray gun, it is heated and cured at 140°C for 1 hour and at 280°C for 1 hour to obtain a coating material.

[0029] Comparative Example 1 The diamine monomer 4,4-diaminodiphenyl ether (6.01 g, 0.03 mol) was added to the dehydrated N,N-dimethylformamide solvent, transferred to a three-necked flask, and nitrogen was introduced for protection. After mechanical stirring, the dianhydride monomer 3,3'4,4'-diphenyl ether tetracarboxylic dianhydride (9.31 g, 0.03 mol) was slowly added in batches to control the total molar amount of dianhydride to diamine monomer to be 1.01:1. Before the anhydride monomer was added, the solution was kept in an ice-water bath environment. After the anhydride monomer was completely added to the solution, the ice-water bath was removed, and the reaction was mechanically stirred at room temperature for 24 hours to obtain a light yellow viscous solution. According to the requirements for the specimen size in the ISO 527:2019 test standard, the modified polyimide film was cured at 140°C for 1 hour and 280°C for 1 hour, and cut into standard tensile test pieces for subsequent tensile tests.

[0030] At the same time, the obtained light yellow viscous liquid is used as the base resin binder, and a mixture of molybdenum disulfide and lanthanum trifluoride (the molar ratio of molybdenum disulfide to lanthanum trifluoride is 4:1) that has been ground and dispersed in advance is compounded as a functional filler, and the total mass ratio of the modified resin binder to the functional filler is controlled to be approximately 3:8. Then, a mixed solvent of N,N-dimethylformamide and N-methylpyrrolidone with a volume ratio of 1:1 is used to adjust the total solid content of the coating to 35%, and a liquid lubricating composite coating is obtained. After the coating is sprayed on a metal substrate with a spray gun, it is heated and cured at 140°C for 1 hour and at 280°C for 1 hour to obtain a coating material.

[0031] Comparative Example 2 The diamine monomer 4,4-diaminodiphenyl ether (10.02 g, 0.05 mol) was added to the dehydrated N,N-dimethylformamide solvent, transferred to a three-necked flask, and nitrogen was introduced for protection. After mechanical stirring, the dianhydride monomer 3,3'4,4'-diphenyl ether tetracarboxylic dianhydride (15.52 g, 0.05 mol) was slowly added in batches to control the total molar amount of dianhydride to diamine monomer to be 1.01:1. Before the anhydride monomer was added, the solution was kept in an ice-water bath environment. After the anhydride monomer was completely added to the solution, the ice-water bath was removed, and the reaction was mechanically stirred at room temperature for 24 h to obtain a light yellow viscous solution. According to the requirements for the specimen size in the ISO527:2019 test standard, the modified polyimide film was cured at 140°C for 1 h and 280°C for 1 h to prepare for subsequent tensile tests.

[0032] At the same time, the obtained light yellow viscous liquid is used as the base resin binder, and a mixture of molybdenum disulfide and lanthanum trifluoride (the molar ratio of molybdenum disulfide to lanthanum trifluoride is 4:1) that has been ground and dispersed in advance is compounded as a functional filler, and the total mass ratio of the modified resin binder to the functional filler is controlled to be approximately 3:8. Then, a mixed solvent of N,N-dimethylformamide and N-methylpyrrolidone with a volume ratio of 1:1 is used to adjust the total solid content of the coating to 35%, and a liquid lubricating composite coating is obtained. After the coating is sprayed on a metal substrate with a spray gun, it is heated and cured at 140°C for 1 hour and at 280°C for 1 hour to obtain a coating material.

[0033] The mechanical properties and tribological properties of the coatings prepared in Examples 1-4 and Comparative Examples 1-2 were compared before and after irradiation. The specific results are as follows: Table 1 Mechanical properties of the unirradiated coating films prepared in Examples 1 to 4 and Comparative Examples 1 to 2 It can be seen from Table 1 that the tensile strength and elongation at break of the modified polyimide films prepared in Examples 1 to 4 are significantly higher than those of the polyimide films prepared in Comparative Examples 1 and 2, and the introduction of fluorine- or boron-containing heteroelement monomers achieves both reinforcement and toughening, which is mainly due to the bridging effect of multiple active reaction points in the fluorine- or boron-containing monomers, which increases the crosslinking density of the polyimide polymer and improves the overall density of the film after curing.

[0034] Table 2 Mechanical properties of the coating films prepared in Examples 1-4 and Comparative Examples 1-2 after 300 and 1000 kGy γ irradiation Table 2 shows the changes in tensile strength and elongation at break of the polyimide films prepared in Examples 1 to 4 and Comparative Examples 1 to 2 after static irradiation with 300 kGy and 1000 kGy gamma rays, respectively. After low-dose gamma ray irradiation, the tensile strength of the modified polyimide films prepared in Examples 1 to 4 generally shows an increasing trend, and the elongation at break decreases. After high-dose irradiation, the tensile strength and elongation at break both decrease, but the degree of decrease is not obvious. This is mainly because the fluorine-containing, boron-containing and hydroxyl groups in the modified polyimide films have a good absorption and annihilation radiation energy effect, and the organic long chains in the polyimide films are interrupted under low-dose gamma ray irradiation, and the small molecular chain segment free radicals formed undergo secondary cross-linking polymerization, which hardens the film, increases the tensile strength, and reduces the elongation at break; while the tensile strength and elongation at break of the polyimide films prepared in Comparative Examples 1 and 2 under high-dose irradiation both show a significant decrease, which is mainly because the polymer segments in the films undergo serious radiation degradation, and the radiation degradation rate is much greater than the cross-linking rate. This shows that the introduction of impurity elements can significantly improve the radiation resistance of polyimide films under high doses.

[0035] Figure 3-5 The figure is a comparison of the tribological properties of the coating films prepared in Examples 1-4 and Comparative Examples 1-2 after 300 and 1000 kGy γ irradiation. As can be seen from the figure, the friction coefficient of the modified polyimide film prepared in Examples 1-4 before and after γ ray irradiation is kept below 0.15, which is better than the polyimide film (0.2-0.25); the wear rate is kept between 7-8, which is also better than the polyimide film (above 10); this shows that the introduction of impurity elements can also improve the friction performance of the polyimide film.

Claims

1. A method for preparing a heteroelement-modified polyimide resin coating resistant to gamma-ray radiation, characterized in that: The method is based on the host-guest condensation reaction strategy, and the heteroelement-containing monomer is introduced into the polyimide precursor in situ to obtain the heteroelement-modified polyimide resin with good radiation resistance. A radiation-resistant lubricating coating with excellent comprehensive mechanical properties and lubrication protection properties is obtained by using a polyimide resin modified by hetero-elements as the base resin binder and compounding it with functional fillers.

2. The method for preparing a γ-ray radiation resistant heteroelement modified polyimide resin coating according to claim 1, characterized in that: The heteroelement-containing monomer is one or two of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 4-aminoformylphenylboronic acid, and 4-aminophenylboronic acid pinacol ester.

3. The method for preparing a heteroelement-modified polyimide resin coating resistant to gamma-ray radiation according to claim 1, characterized in that: The polyimide precursor is a mixture of a diamine monomer 4,4-diaminodiphenyl ether and a dianhydride monomer 3,3'4,4'-diphenyl ether tetracarboxylic dianhydride.

4. The method for preparing a γ-ray radiation resistant heteroelement modified polyimide resin coating according to claim 1, characterized in that: The in-situ introduction process is as follows: dissolving the diamine monomer 4,4-diaminodiphenyl ether and the monomer containing heteroelements in an organic solvent and stirring to mix them evenly, then adding the dianhydride monomer 3,3'4,4'-diphenyl ether tetracarboxylic dianhydride in batches under nitrogen protection, and stirring to react at -20-15°C for 20-30h.

5. The method for preparing a heteroelement-modified polyimide resin coating resistant to gamma-ray radiation according to claim 4, characterized in that: The molar ratio of the diamine monomer to the monomer containing heteroelements is 2:1-18:1, and the molar ratio of the dianhydride monomer to the diamine monomer is 1:1-1.5:

1.

6. The method for preparing a heteroelement-modified polyimide resin coating resistant to gamma-ray radiation according to claim 4, characterized in that: The organic solvent is N,N-dimethylformamide or N,N-dimethylacetamide that has been dehydrated.

7. The method for preparing a heteroelement-modified polyimide resin coating resistant to gamma-ray radiation according to claim 1, characterized in that: The specific preparation process of the radiation-resistant lubricating coating is as follows: using heteroelement-modified polyimide resin as a base resin binder, a mixture of molybdenum disulfide and lanthanum trifluoride that has been ground 2 to 3 times on a conical mill in advance as a functional filler, and a mixed solvent of N,N-dimethylformamide and N-methylpyrrolidone as a diluent, and obtaining a radiation-resistant lubricating coating with a solid content of 30% to 40% after high-speed shearing.

8. The method for preparing a heteroelement-modified polyimide resin coating resistant to gamma-ray radiation according to claim 7, characterized in that: The molar ratio of molybdenum disulfide to lanthanum trifluoride is 3:1-5:1, and the volume ratio of N,N-dimethylformamide to N-methylpyrrolidone is 1:2-2:

1.

9. Use of the heteroelement-modified polyimide resin coating resistant to gamma-ray radiation prepared by the method of claim 1 in radiation-resistant coating.

10. The use of the heteroelement modified polyimide resin coating resistant to gamma ray radiation as claimed in claim 9 in an anti-radiation coating, characterized in that: The specific preparation process of the radiation-resistant coating is as follows: the coating is sprayed on the metal substrate by a spray gun, and then kept at 130-150° C. for 1-2 hours, and heated and cured at 270-290° C. for 1-2 hours to obtain the coating.

Citation Information

Patent Citations

  • Neutron radiation-resistant polyimide coating and preparation method and application thereof

    CN110240862A

  • Method for preparing anti-radiation polyimide composite membrane

    CN110551281A

  • Radiation-resistant polyimide with sandwich structure as well as preparation method and application of radiation-resistant polyimide

    CN114316324A

  • High-temperature-resistant polyimide adhesive based on dynamic boron-oxygen bonds and preparation method of high-temperature-resistant polyimide adhesive

    CN116574477A

  • Polyimide base high temp.-resistant and radiation-resistant lubricating paint

    CN1385487A

Cited By

  • Transparent cross-linked polyimide film and preparation method thereof

    CN119955136A